EXPERIMENTATION AND MODELLING FOR COLOCASIA ESCULENTA (L.) SCHOOT SLICES DRYING PROCESS - AI S. ZHU; YAN W. SHI; DA Z. TAO; MAO Q. XU; JUN Z. ZHAO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The effects of drying air temperature, air velocity and slices thickness on the drying behavior of Colocasia esculenta (L.) Schoot slices were investigated in a convective hot air tunnel dryer. Mass transfer during the drying was described using six models and the models performances were evaluated. The effective diffusion coefficients (Deff) were calculated and the temperature dependency of Deff was illustrated. The results showed that the drying took place in main falling rate period; the Logarithmic model showed good agreement with all experiments data; at the varied range of temperature the Deff values varied from 4.94×10-10 to 6.86×10-10 m2·s-1 and it fitted the Arrhenius equation, the activation energy was 16.15 kJ·mol-1; with the increase of hot air velocity from 0.5 to 1.5 m·s-1, the Deff varied from 4.51×10-10 to 6.68×10-10 m2·s-1; for slices thickness 1, 2 and 3 mm, the Deff was 1.69×10-10, 5.76×10-10 and 9.81×10-10 m2·s-1 respectively.